2015
DOI: 10.3844/ajnsp.2015.31.39
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesized Silver Nanoparticles Prepared from the Antimicrobial Crude Extracts of two Brown Seaweeds Against Plant Pathogens

Abstract: This study aimed for green synthesis of silver nanoparticles (Ag-NPs) from the antimicrobial crude extracted in chloroform: methanol(1:1 v/v) from the two brown seaweeds Spatoglossum asperum and Hedophyllum sessile active against two pathogenic bacteria (Xanthomonas axonopodis pv. citri and X. oryzae pv. oryzae) and a fungus Ustilaginoidea virens cause diseases in plants under in vitro assay. Crude extracts exhibit high antibacterial activity and low antifungal activity. Green synthesized Ag-NPs showed very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nowadays, nanotechnology seems a promising revolution in the construction and characterization of the functional properties of the nanoparticles to incur into different branches of sciences ( Jothirethinam et al., 2015 ). Basil (Ocimum basilicum L) is an herb widely used in folk medicine, food flavoring.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, nanotechnology seems a promising revolution in the construction and characterization of the functional properties of the nanoparticles to incur into different branches of sciences ( Jothirethinam et al., 2015 ). Basil (Ocimum basilicum L) is an herb widely used in folk medicine, food flavoring.…”
Section: Introductionmentioning
confidence: 99%
“…68,69 There are studies that have reported AgNPs synthesized using crude extracts of marine brown algae such as Sargassum wightii, 70 Turbinaria conoides, 71 and other seaweeds. 23,72,73 In this study, the synthesis of AgNPs by sulfated fucoidan isolated from the marine brown alga T. decurrens was confirmed based on the colorless solution of AgNO 3 turning brownish-yellow, indicating the formation of NPs, and monitored by the UV− visible spectral band at 420 nm (Figures 5a and S2). This band was identified as a "surface plasmon resonance band" attributed to the excitation of free electrons in the NPs.…”
Section: Resultsmentioning
confidence: 65%
“…NPs synthesized by selective biomolecules are considered to be most desired for target-specific biomedical applications rather than those synthesized from crude compounds. , There are studies that have reported AgNPs synthesized using crude extracts of marine brown algae such as Sargassum wightii, Turbinaria conoides, and other seaweeds. ,, In this study, the synthesis of AgNPs by sulfated fucoidan isolated from the marine brown alga T. decurrens was confirmed based on the colorless solution of AgNO 3 turning brownish-yellow, indicating the formation of NPs, and monitored by the UV–visible spectral band at 420 nm (Figures a and S2).…”
Section: Resultsmentioning
confidence: 68%
“…Many of the physical and chemical properties of nanoparticles can be controlled by choosing their size and shape. Since nanoparticles (NPs) could be used in optoelectronics, recording media, sensing devices, catalysis, and medicine, producing and studying them is an important area of research [ 2 ]. Chemical methods used to produce nanoparticles today cannot be used in biomedicine because they use toxic chemicals and produce harmful byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic systems include the use of yeast, fungi, bacteria, plants, and other organisms to produce nanostructures of metals and semiconductors that are safe for living things. Silver nanoparticles (Ag-NPs) are becoming more popular as more pathogens become resistant to antibiotics [ 2 , 4 ]. As a possible antimicrobial agent, metallic silver in the form of nanoparticles has received significant attention [ 5 ].…”
Section: Introductionmentioning
confidence: 99%